Empirical Investigation on Globalization and Social Polarization: Cross Country Analysis - Koç, Aylin; Ata, Ahmet Yılmaz; Çirkin, Zeynep (International Journal of Economics and Financial Issues, 2012)
It is considered that the integration process of both developed and developing countries with the global world affects the aspect of social polarization in these countries. Two main approaches which are different from each other exist in the related literature about the effects of globalization on the social polarization. The first approach, which is mostly supported by neo-liberal economists, claims that the globalization influences the social polarization positively. The other approach suggests that the social polarization increases in the economies together with the globalization process. With this study which was prepared in this scope, the effect of globalization process on the social polarization was tried to be tested by cross-sectional analysis of the data of 2008 of twenty-seven EU member countries. As a result of the findings obtained in this study, it was concluded that the globalization process has a decreasing effect on the social polarization in these countries. Keywords: Social Polarization; Globalization; Income Distribution JEL Classifications: D02; D40; D72; D73; D82